PERAN GURU DALAM IMPLEMENTASI PEMBELAJARAN BERBASIS DATA - Komara Nur Ikhsan; Mumuh Muhtarom (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT Teachers have an important role in improving the quality of learning through the utilization of student evaluation data. This study aims to analyze the role of teachers in implementing data-driven learning in educational settings. The study employed a qualitative descriptive method using a literature review approach through the analysis of scientific journals, reference books, and relevant articles related to data-driven learning. The findings indicate that teachers play a significant role in collecting, analyzing, and utilizing evaluation data to determine learning strategies that align with students’ needs. The use of data helps teachers identify students’ abilities, learning difficulties, and academic progress, thereby making the learning process more effective, adaptive, and student-centered. In addition, data-driven learning supports the provision of more targeted teaching materials and learning support to create an inclusive learning environment. This study emphasizes that data-driven learning not only enhances the effectiveness of the learning process but also strengthens teachers’ pedagogical decision-making in a systematic and sustainable manner. The conclusion of this study shows that the role of teachers in data-driven learning is highly important in supporting the improvement of learning quality and optimizing students’ development. ABSTRAK Guru memiliki peran penting dalam meningkatkan kualitas pembelajaran melalui pemanfaatan data hasil evaluasi peserta didik. Penelitian ini bertujuan untuk menganalisis peran guru dalam menerapkan pembelajaran berbasis data di lingkungan pendidikan. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan studi literatur melalui kajian jurnal ilmiah, buku referensi, dan artikel relevan terkait pembelajaran berbasis data. Hasil penelitian menunjukkan bahwa guru berperan dalam mengumpulkan, menganalisis, dan memanfaatkan data evaluasi untuk menentukan strategi pembelajaran yang sesuai dengan kebutuhan peserta didik. Pemanfaatan data membantu guru mengidentifikasi kemampuan, hambatan belajar, dan perkembangan siswa sehingga proses pembelajaran menjadi lebih efektif, adaptif, dan berpusat pada peserta didik. Selain itu, pembelajaran berbasis data mendukung penyediaan bahan ajar dan layanan pembelajaran yang lebih tepat sasaran guna menciptakan lingkungan belajar yang inklusif. Penelitian ini menegaskan bahwa pembelajaran berbasis data tidak hanya meningkatkan efektivitas proses pembelajaran, tetapi juga memperkuat pengambilan keputusan pedagogis guru secara sistematis dan berkelanjutan. Simpulan penelitian menunjukkan bahwa peran guru dalam pembelajaran berbasis data sangat penting dalam mendukung peningkatan kualitas pembelajaran dan perkembangan peserta didik secara optimal.